A new variant of Carney's triad: phaeochromocytoma and chondrosarcoma. Issue 910 (1st August 2001) - Wahid, S T; Jones, R; Chawla, S L; Connolly, V M; Kelly, W F; Bilous, R W
Abstract : A 61 year old hypertensive woman presented in 1986 with a right scapular chondrosarcoma. She developed type 1 diabetes mellitus in 1991 and suffered a stroke in 1991. Chest radiography showed pulmonary metastases in 1997. Further radiological staging detected a right sided phaeochromocytoma, which was subsequently removed in 1998. Before this, repeated urine estimations of vanillylmandelic acid had been normal. Her diabetes was cured by adrenalectomy. It is believed that the combination of phaeochromocytoma and extrapulmonary chondrosarcoma represents a new variant of Carney's triad.